PENGEMBANGAN MODEL PEMBELAJARAN SEPAKBOLA DENGAN PERMAINAN "BALANGKA" DALAM PENJASORKES KELAS VIII SMP NEGERI 1 KOTA SEMARANG TAHUN PELAJARAN 2013/2014 - Brity Bambang Andrian; H.Cahyo Yuwono (Universitas Negeri Semarang, 2015)
This research aims to determine the results of learning model development through the game of football balangka for eighth grade students of SMP Negeri 1 Semarang in learning Physical education and Health The method of this research is to development refers to developing of the model. (research-based devolepment) by Brog and Gall that has been modified. The data was collected by a questionnaire derived from, expert evaluation, observation sheet student movement, a small test group (12 students), and range tests (30 students). Research data, expert evaluation data that experts phisical education 80% (it means good), learning experts 89.33% (it means excellent), observational data motion test students' small group 92.67% (it means excellent), observational data field test student movement, 96.67% (it means very good), a small group of test result data from the student questionnaire obtained a percentage of 86.67% (excellent), the data from the field test results of the student questionnaire obtained a percentage 84.89% (it means excellent). Based on the results in above , the concluded is balangka game development learning model is compatible to applied for both eighth grade students of SMP Negeri 1 Semarang.